PREVALENCE OF mcr-1 COLISTIN-RESISTANT GENE IN Escherichia coli ALONG THE BROILER MEAT SUPPLY CHAIN IN INDONESIA - Maria Fatima Palupi; I Wayan Teguh Wibawan; Etih Sudarnika; Hera Maheshwari; Huda Shalahudin Darusman (SEAMEO BIOTROP, 2019)
Colistin is the last drug of choice for dealing with carbapenem-resistant Enterobacteriaceae bacteria; hence, this drug is very crucial to human health. The discovery of a plasmid-mediated colistin-resistant gene, the mobilized colistin resistance-1 (mcr-1), signals a significant global health threat. Colistin sulfate is an antimicrobial agent which has been approved for use in broilers in Indonesia. Thus, this study aimed to measure the prevalence of colistin-resistant Escherichia coli and to detect the mcr-1 colistin-resistant gene in E. coli and E. coli O157:H7 in the entire supply chain of broilers in Bogor Regency, West Java Province, Indonesia. Samples were taken from 47 flocks that used colistin sulfate (47 pools of cloacal swabs, 47 pools of drinking water, and 47 pools of litter), seventy fresh meat samples and seven plucker swab samples from seven small-scale poultry slaughterhouses, seventy fresh meat samples from seven traditional markets, and seventy cooked meat samples from seven small restaurants. The isolation of E. coli was done on each of the 358 samples, and 493 isolates were obtained. All the E. coli isolates were then tested for their susceptibility to colistin sulfate by using the agar dilution method. The detection of the mcr-1 gene from the colistin-resistant isolates (minimum inhibitory concentration > 2 µg/mL) was conducted using the polymerase chain reaction (PCR). The prevalence value of colistin-resistant E. coli in all the isolates was 11.76% (CI 95%; CL 9.21–14.91), and the prevalence of the mcr-1 gene was 10.55% (CI 95%; CL 8.13–13.57%). A very good agreement correlation existed between the colistin-resistant phenotype and the mcr-1 gene (κ = 0.939). The mcr-1 gene was found in 89.66% of colistin-resistant E. coli isolates. Two colistin-resistant and mcr-1 carrying isolates were identified as E. coli O157:H7 serotype. This research was the first study attempt on the mcr-1 gene in Indonesia, covering the entire supply chain of broiler meat from farms to consumers. The results indicated the necessity to reduce the use of colistin sulfate in broiler management and to improve biosecurity measures, not only in farms but also in the entire supply chain of broiler meat production.